DELINEASI CEKUNGAN SEDIMEN SUMATRA SELATAN BERDASARKAN ANALISIS DATA GAYA BERAT - Imam Setiadi; Budi Setyanta; Bambang Suci Widijono (Pusat Survei Geologi, 2010)
South Sumatra Basin is one of large sedimentary basins in Indonesia which has been proven to produce hydrocarbon energy. Several literatures mention different amount of subbasin with this basin. Gravity is one of geophysical methods that is used to interpret lateral and vertical basin configuration based on rock density parameter. The gravity analysis is conducted by using spectral analysis method in order to estimate shallow and depth anomaly sources, and then to separate regional and residual anomaly using moving average method. The result of spectrum analyses show two discontinuity density plans, located at 3.05 km reflecting the average depth of Tertiary sedimentary basement, and at 15.98 km reflecting Moho discontinuity plane. Meanwhile, the residual anomaly shows that there are two lineament patterns trending northwest-southeast and southwest- northeast. The main fault is Sumatra Fault indicating northwest-southeast lineament, and the subsidiary faults trending southwest-northeast. Azimuth of shallow basement and rifting patterns are northwest-southeast, while the number of identified subbasin are 10. The result of two dimensional modeling shows that the basement in South Sumatra is metamorphic rock having the density contrast 0.12 gr/cc and the average density contrast of the sedimentary rocks filling the basin is -0.22 gr/cc.Keywords : gravity, spectral analyses, moving average, South Sumatra Basin